Pengaruh pendapatan asli daerah, dana alokasi umum dan dana alokasi khusus terhadap belanja modal pada kabupaten/kota di Provinsi Jambi - Vanesha, Venny Tria; Rahmadi, Selamet; Parmadi, Parmadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to analyze the development of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Spesific Allocation Fund (DAK), and capital expenditure as well as the influence of PAD, DAU and DAK on capital expenditure in districts/cities in Jambi Province. Data is sourced from the Directorate-General of Regional Fiscal Balance, the Ministry of Finance of the Republic of Indonesia. Data were analyzed using panel data regression models. The results of the study found that simultaneously PAD, DAU, DAK had a significant effect on capital expenditure. However, only partially the DAU influences the capital expenditure of districts/ cities in Jambi Province.